Peningkatan Kemampuan Komunikasi Matematis Model Ideal Problem Solving dalam Aspek Grammatical dan Sosiolinguistik - Akhmad Nayazik; Arie Wahyuni (Didaktik Matematika, 2017)
The importance of learning mathematics can not be separated from its role in all aspects of everyday life. Communicating ideas using language and mathematical notation is even more practical, systematic, and efficient. Recognizing the importance of mathematical communication skills then as a prospective educator should seek learning that can provide opportunities and encourage students to trained the ability of mathematical communication. Indicator of mathematical communication ability in this research include grammatical ability (K1) and sociolinguistic ability (K2). The subject of high school mathematics curriculum is a compulsory course that must be taken, because it will be discussed about the subject matter of school math and various models. One of the learning model that meets the indicator of mathematical communication ability is IDEAL Problem Solving model.This study aims to improve the ability of mathematical communication in grammatical and sociolinguistic aspects. The type of research used is classroom action research based on Stephen Kemmi and Robin Mc Taggart models. From the result of the research, it is found that the application of IDEAL Problem Solving model of high school mathematics curriculum can improve mathematical communication ability in grammatical (K1) and sociolinguistic (K2) aspect. The percentage of grammatical aspect (K1) increased from 78% to 89% and sociolinguistic aspects (K2) increased from 81% to 89%.